Legenda Buka Luwur Asal-Usul Dukuh Pantaran sebagai Media Pendidikan Karakter - Jeni Nur Cahyati; Zainal Arifin (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to (1) describe the description of the legend of Buka Luwur the origins of Dukuh Pantaran, and (2) describe the potential of the legend of Buka Luwur the origins of Dukuh Pantaran as a medium for character education. This research is a qualitative descriptive study. The data in this study are words, phrases, clauses, and sentences that contain the value of character education in the legend of Buka Luwur the Origin of Dukuh Pantaran. Data sources consist of primary and secondary. Data collection techniques using observation, interview, recording, recording, and document analysis techniques. The data validation used source triangulation. Data analysis techniques with interactive models. The results of this research are (1) the legend of Buka Luwur The origin of the Pantaran Hamlet is a type of folklore legend because it tells the origin of the name Dukuh Pantaran; and (2) the legend of Buka Luwur the origins of Dukuh Pantaran contain fourteen values ​​of character education, namely: religious, honest, tolerance, discipline, hard work, creative, independent, curiosity, respect for achievement, friendly/communicative, love, peaceful, environmental care, social care, and responsibility. With these fourteen values, the legend of Buka Luwur the origins of Dukuh Pantaran has the potential as a character education medium that needs to be instilled in students.